2018
DOI: 10.1155/2018/8678124
|View full text |Cite
|
Sign up to set email alerts
|

Exploitation of Ultrahigh‐Performance Fibre‐Reinforced Concrete for the Strengthening of Concrete Structural Members

Abstract: e repair and strengthening of reinforced concrete members are very important due to several factors, including unexpected increases in load levels and/or the damaging impact of aggressive environmental conditions on structural concrete members. Many researchers have turned to using materials for the repair and strengthening of damaged structures or the construction of new concrete structural members. Ultrahigh-performance fibre-reinforced concrete (UHPFRC), characterized by superior structural and durability p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 30 publications
(48 reference statements)
0
9
0
Order By: Relevance
“…A photo of the damaged beam after cleaning is shown in Figure 3 a . Note that the surfaces could be roughened through sandblasting which proved to be a viable solution when applying it to the parent concrete surface before strengthening ( 6 ).…”
Section: Repair Of the Damaged Beamsmentioning
confidence: 99%
See 1 more Smart Citation
“…A photo of the damaged beam after cleaning is shown in Figure 3 a . Note that the surfaces could be roughened through sandblasting which proved to be a viable solution when applying it to the parent concrete surface before strengthening ( 6 ).…”
Section: Repair Of the Damaged Beamsmentioning
confidence: 99%
“…In all cases, results showed that the strengthening/repair methods lead to higher stiffness, increased capacity, and delayed crack formation and propagation. A literature review of research studies and practical applications on the repair and strengthening of concrete members using high-strength and high-performance concretes is reported by Al Osta ( 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…The aforementioned literature review reveals that the majority of the conducted research is focused on the application of nonconventional jackets in strengthening methods of original RC structural members [17][18][19]21,22,24,[26][27][28][30][31][32][33][34]36,[38][39][40][41][42][43][44][45][48][49][50]56]. Significantly fewer studies investigate such jackets for the repair of preloaded and slightly damaged RC specimens [20,23,25,29,35,37,46,47,[51][52][53][54][55].…”
Section: Research Significancementioning
confidence: 99%
“…These reasons have led researchers to switch to new jacketing techniques with alternative materials such as steel [17][18][19], advanced materials such as fiber reinforced polymer (FRP) [20][21][22][23][24][25], textile reinforced concrete or mortar [26][27][28][29] and shape memory alloys [30][31][32], cement-based materials such as ferrocement [33][34][35][36], steel fibrous concrete or mortar [37][38][39][40], high-performance fiber reinforced concrete [41][42][43][44][45][46][47][48], self-compacting concrete (SCC) [49][50][51][52][53][54], and thin slightly reinforced flowable mortar [55,56]. Many of these jacketing techniques have been proved successful substitutes to common RC jacketing.…”
Section: Introductionmentioning
confidence: 99%
“…This type of concrete is chosen because it exhibits high strength and durability minimizing the need for future maintenance . Al‐Osta and Brühwiler and Denarié reported that UHPFRC has a compressive strength of more than 170 MPa, a flexural strength higher than 30 MPa, and a tensile strength over 8 MPa. Its strength is superior to that of the existing conventional concrete making it a perfect choice to be used as a repair material.…”
Section: Introductionmentioning
confidence: 99%